Level of Knowledge and Attitude of Nurses as First esponders in an In-Hospital Cardiac Arrest Event - Rafiqi, Sandi Ihsan; Khoiriyati, Azizah (Universitas Muhammadiyah Yogyakarta, 2025)
Introduction - In-hospital cardiac arrest (IHCA) is an emergency condition that can threaten a person's life if not treated immediately. Sufficient nurses’ knowledge and attitude may lead to successful IHCA prevention and handling. Purpose - This study aims to determine the level of knowledge and attitude of nurses at PKU Muhammadiyah Hospital Yogyakarta in handling IHCA. Methodology - Research method uses a quantitative descriptive research design. One hundred nurses from the adult care ward of a hospital in Yogyakarta, Indonesia were recruited using the purposive sampling technique. This research was conducted from December 2023 to March 2024. The research instrument used was a nurse level of knowledge questionnaire and a nurse attitude questionnaire. Findings - Most of the nurses has good knowledge (73 respondents (73%)) and attitude (94 respondents (94%)) as first responders during cardiac arrest events. There are still errors in answering the BLS algorithm points and airway and breathing management. Conclusion - Level of knowledge and attitude of nurses is in the good category. This research can be used as material for evaluating nurses when treating cardiac arrest patients in hospitals.